IMPLEMENTATION OF LECTURERS’' PERFORMANCE DURING PANDEMIC COVID 19 SITUATIONS AT HIGHER EDUCATION IN EAST KALIMANTAN - Muhammad Adenuddin Alwy, SE., MM; Dr. Rachmie Sari Baso, SS. M.Educ Stds.MEd. (PENERBIT LAFADZ JAYA, 2022)
The purpose to be achieved in this research is to find out how the implementation of lecturers’ performance during the Covid-19 pandemic at higher education in East Kalimantan. The method used in this research is a literature study. Data was collected through a study of relevant texts and research results. Data analysis was carried out with the following steps: First, the data that had been collected were classified based on the formulation of the problem under study. Second, the data studied were qualitatively analyzed using content analysis. Third, based on the results of data analysis and interpretation, conclusions are drawn along with suggestions. The results of the study show that, First, the implementation of lecturers’ performance during the Covid-19 pandemic is divided into three discussions, namely: (1) lecturers' performance factors; (2) learning management in improving the quality of education; (3) lecturers’ performance in managing learning. The conclusion of this study is the optimization of Llecturers’ performance seen from how lecturers’ prepare themselves, both facilities and infrastructure in carrying out learning from home.